2006
DOI: 10.1001/jama.296.22.2703
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in the CRP Gene With Circulating C-Reactive Protein Levels and Cardiovascular Events

Abstract: Genetic variation in the CRP gene is associated with plasma CRP levels and CVD risk in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
199
3
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(237 citation statements)
references
References 46 publications
(44 reference statements)
31
199
3
3
Order By: Relevance
“…These haplotypes form a distinct phylogenetic clade, thus strengthening our argument that a major functional SNP lies on this branch of the haplotype tree. The association of rs1205 with basal CRP has been reported previously, and studies generally confirm that haplotypes containing the rare allele of rs1205 are associated with low basal CRP (Crawford et al, 2006;Kathiresan et al, 2006;Lange et al, 2006b;Miller et al, 2005;Russell et al, 2004). We therefore extend this finding to a group of linked SNPs delineating "low-producing" haplotypes.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These haplotypes form a distinct phylogenetic clade, thus strengthening our argument that a major functional SNP lies on this branch of the haplotype tree. The association of rs1205 with basal CRP has been reported previously, and studies generally confirm that haplotypes containing the rare allele of rs1205 are associated with low basal CRP (Crawford et al, 2006;Kathiresan et al, 2006;Lange et al, 2006b;Miller et al, 2005;Russell et al, 2004). We therefore extend this finding to a group of linked SNPs delineating "low-producing" haplotypes.…”
Section: Discussionsupporting
confidence: 74%
“…A possible explanation for the erratic association between CRP and disease is that polymorphism at CRP itself (or at least the variants we are measuring), actually only explains a relatively small proportion of CRP variation, compared with other environmental or trans-acting genetic factors; thus even large studies are underpowered. This has indeed been hinted at in existing regression-based analyses where the partial r 2 for associated CRP polymorphisms has been <3% (Crawford et al, 2006;Kathiresan et al, 2006;Lange et al, 2006b). Of potential trans-acting influences, variation at the acute-phase cytokine genes interleukin-1β (IL1B) and interleukin-6 (IL6) and also apolipoprotein E (APOE) has been associated with basal CRP, albeit inconsistently (Berger et al, 2002;Chasman et al, 2006;Eklund et al, 2005;Judson et al, 2004;Lange et al, 2006a;Latkovskis et al, 2004;Marz et al, 2004;Paik et al, 2007;Shin et al, 2007;Vickers et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, several large population-based studies showed that plasma CRP levels are under genetic influence (20 -25). Some of these polymorphisms have been consistently associated with CRP levels (higher levels associated with rs3093058_T and lower levels associated with rs1205_A and rs2808630_G) and the risk of cardiovascular events (rs3093058_T) in African Americans (23).…”
mentioning
confidence: 99%
“…When allele G changed into C in rs1800947, circulating CRP of genotype GG carrier individual is higher than genotype CC carrier in healthy individuals (Suk et al, 2005;Lange et al, 2006;Kivimäki et al, 2007;Chaturvedi et al, 2010) and thoracic esophageal cancer patients after exophagectomy (Motoyama et al, 2009). It suggested that cancer patients with genotype CC carrier shared a lower serum level of CRP than GG carrier.…”
Section: Discussionmentioning
confidence: 99%